An integrated analysis of bulk and single-cell sequencing data reveals that EMP1+/COL3A1+ fibroblasts contribute to the bone metastasis process in breast, prostate, and renal cancers - Du, Haoyuan; Wang, Hua; Luo, Yuwei; Jiao, Yang; Wu, Jiajun; Dong, Shaowei; Du, Dong (Frontiers in Immunology, 2023)
This is a provisional file, not the final typeset article Bone metastasis (BoM) occurs when cancer cells spread from their primary sites to a bone. Currently, the mechanism underlying this metastasis process remains unclear. In this study, through a combined analysis of bulk-sequencing data and single-cell RNA sequencing data, we first identified 34 upregulated genes during the BoM process in breast cancer, and further explored their expression status among different components in the tumor microenvironment (TME) of breast cancer BoM samples.Enriched EMP1 + fibroblasts were found in BoM samples, and a COL3A1-ADGRG1 communication between these fibroblasts and cancer cells was identified which might facilitate the BoM process.Moreover, there is a significant positive correlation between the expression of EMP1 and COL3A1 in these fibroblasts, confirming the potential connection of these genes during the BoM process.Furthermore, the existence of these EMP1 + /COL3A1 + fibroblasts was also verified in prostate cancer and renal cancer BoM samples, suggesting the importance of these fibroblasts from a pan-cancer perspective. This study is the first attempt to explore the relationship between fibroblasts and cancer BoM across multi-tumor TMEs. Our results might shed some light on the exploration of the cancer BoM mechanism while providing some potential targets for future treatments of tumor metastasis.